Phytomass and carbon deposited by black locust stands within Northern Steppe of Ukraine - Sytnyk, S. A.; Lakyda, P. I. (Forestry and Forest Melioration, 2020)
Introduction Under global climate change, a particular attention is paid to the research of quantitative changes in carbon flows and pools in forest ecosystems. As a change in the carbon dioxide concentration in the atmosphere has been reported, it is necessary to study the role of forests which make the most powerful reservoir of atmospheric carbon accumulation in the aboveground phytomass of stands. A particularly urgent task is to study carbon-sequestrating properties of forest-forming tree species in the steppe zone, where the forest cover is the lowest in Ukraine and the list of tree species used for planting forest stands is the poorest. Pure planted stands of Robinia pseudoacacia L. are widely represented in the forests managed by the State Forest Resources Agency of Ukraine within Ukrainian Northern Steppe. Those occupy an area of 17,683.7 hectares in Dnipropetrovsk Region. The aim of the research was to evaluate the dynamics of total phytomass and carbon sequestered in the black locust stands in Ukrainian Northern Steppe. The black locust stands growing in the steppe zone were the object of the research. The subject of the research were phytomass and carbon sequestered by the black locust stands. Materials and Methods The initial data for the estimation of the total amounts of the phytomass, distribution by structural components and carbon sequestration in the black locust stands are represented by forest management planning materials (1973, 1978, 1983, 1996, 2002, 2011) of forests managed by the Dnipropetrovsk Regional Department of Forestry and Hunting, namely: areas of the black locust stands, their growing stock, age structure and a mean site index class. The actual research data were processed using Excel and Carbon application developed by Lakyda (2002). The Carbon application involves calculation and integration of the total phytomass of forest stands (million tons) within the administrative region based on the following phytomass components: wood and bark of stems, wood and bark of crown branches, foliage, roots, understorey. Moreover, it can calculate a phytomass density and carbon (kg·(m2)-1). Results and Conclusions As of January 1, 2011, phytomass of the stands in the study area reached almost 2.0 million tons, in which up to 0.98 million tons of carbon had been accumulated. During the period of 38 years, the area of the black locust stands increased from 10.8 to 17.6 thousand m2. During the audit period there was a regular intensive increase of the total growing stock of stem wood from 0.27 to 2.73 million m3. As compared to 1973, in 2011, phytomass of the black locust stands increased by 226.8 %. The increase is caused by the changes in the age structure of the stands, which led to the predominance of mature and overmature forests. In the structure of the total phytomass of the black locust stands, a fraction of wood and bark of stems (64.4–68.9%) is the largest, while understorey (2.2–3.6 %) makes the smallest fraction. Growth and formation of the black locust stands during three decades has led to a slight redistribution of the phytomass fractions between their structural components. During the period from 2004 to 2018, the maximum amounts of technogenic carbon (35.6–37.7 million tons per year) emitted into open air in Dnipropetrovsk Region were observed in 2011–2014. The average annual amount of the emission was 27.7 million tons. The carbon accumulated in the phytomass of the studied stands was from 0.3466 (1973) to 0.9789 million tons (2011). The change in the average carbon density of the forest covered land occupied by the black locust stands during the accounting period was (kg·(m2)-1): 1973 – 3.21; 1978 – 3.30; 1983 – 3.91; 1996 – 4.41; 2002 – 5.39; 2011 – 5.56. The increase in accumulated carbon density in the black locust stands within one year ranges from 0.02 to 0.11 kg·(m2)-1. It was found that black locust stands in Ukrainian Northern Steppe can sequester a very small part of the technogenic carbon emissions, namely from 0,01% to 0,07%. At an average annual volume of carbon dioxide emissions into the atmosphere of the study region 27.7 million tons and an annual increase in carbon density in the black locust stands in Ukrainian Northern Steppe may deposit an insignificant part of man-made carbon emissions, namely 0.01–0.07%. 2 Figs., 2 Tables, 22 Refs. Key words: Robinia pseudoacacia, total stand phytomass, structural components of phytomass, carbon pool.